Determining the Plasmodium vivax VCG-1 strain blood stage proteome (2015)
Plasmodium vivax is the second most prevalent parasite species causing malaria in humans living in tropical and subtropical areas throughout the world. There have been few P. vivax proteomic studies to date and they have focused on using clinical isolates, given the technical difficulties concerning how to maintain an in vitro culture of this species. This study was thus focused on identifying the P. vivax VCG-1 strain proteome during its blood lifecycle through LC-MS/MS; this led to identifying 734 proteins, thus increasing the overall number reported for P. vivax to date. Some of them have previously been related to reticulocyte invasion, parasite virulence and growth and others are new molecules possibly playing a functional role during metabolic processes, as predicted by Database for Annotation, Visualization and Integrated Discovery (DAVID) functional analysis. This is the first large-scale proteomic analysis of a P. vivax strain adapted to a non-human primate model showing the parasite protein repertoire during the blood lifecycle. Database searches facilitated the in silico prediction of proteins proposed for evaluation in further experimental assays regarding their potential as pharmacologic targets or as component of a totally efficient vaccine against malaria caused by P. vivax. Biological significance: P. vivax malaria continues being a public health problem around world. Although considerable progress has been made in understanding genome- and transcriptome-related P. vivax biology, there are few proteome studies, currently representing only 8.5% of the predicted in silico proteome reported in public databases. A high-throughput proteomic assay was used for discovering new P. vivax intra-reticulocyte asexual stage molecules taken from parasites maintained in vivo in a primate model. The methodology avoided the main problem related to standardising an in vitro culture system to obtain enough samples for protein identification and annotation. This study provides a source of potential information contributing towards a basic understanding of P. vivax biology related to parasite proteins which are of significant importance for the malaria research community. © 2014 .